A high-throughput screening to identify small molecules that suppress huntingtin promoter activity or activate huntingtin-antisense promoter activity - Houda G. Khaled (Nature Portfolio, 2021)
Abstract Huntington’s disease (HD) is a neurodegenerative disorder caused by a CAG repeat expansion in exon 1 of huntingtin (HTT). While there are currently no disease-modifying treatments for HD, recent efforts have focused on the development of nucleotide-based therapeutics to lower HTT expression. As an alternative to siRNA or oligonucleotide methods, we hypothesized that suppression of HTT expression might be accomplished by small molecules that either (1) directly decrease HTT expression by suppressing HTT promoter activity or (2) indirectly decrease HTT expression by increasing the promoter activity of HTT-AS, the gene antisense to HTT that appears to inhibit expression of HTT. We developed and employed a high-throughput screen for modifiers of HTT and HTT-AS promoter activity using luminescent reporter HEK293 cells; of the 52,041 compounds tested, we identified 898 replicable hits. We used a rigorous stepwise approach to assess compound toxicity and the capacity of the compounds to specifically lower huntingtin protein in 5 different cell lines, including HEK293 cells, HD lymphoblastoid cells, mouse primary neurons, HD iPSCs differentiated into cortical-like neurons, and HD hESCs. We found no compounds which were able to lower huntingtin without lowering cell viability in all assays, though the potential efficacy of a few compounds at non-toxic doses could not be excluded. Our results suggest that more specific targets may facilitate a small molecule approach to HTT suppression.